2004
DOI: 10.1087/095315104322958490
|View full text |Cite
|
Sign up to set email alerts
|

Institutional repositories and scholarly publishing

Abstract: The institutional repository (IR), an open Web‐based archive of scholarly material produced by the members of a defined institution, has come to the fore following the launch of DSpace at MIT at the end of 2002. Here we review recent developments in IRs and explore the impact their expansion may have on scholarly publishing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(36 citation statements)
references
References 3 publications
1
31
0
4
Order By: Relevance
“…The other reasons that were highly ranked included: the likelihood that open access publications would be misused or plagiarised (51%); the general perception that open access publications were of low quality compared to traditional publications (55,2%); and researchers' worry about the long-term availability of open access publications (35,4%). These findings corroborate previous studies that found that uncertainties over later publishing of open access articles elsewhere, violation of publishers' copyrights, and plagiarism of open access papers are among the cited respondents' deterrents for their contribution to institutional repositories (Fang and Zhu 2006;Foster and Gibbons 2005;Hirwade and Rajyalakshmi 2005;Kim 2006;Pickton 2005;Ware 2004;Xu 2005). It is necessary to address these challenges to foster the adoption of open access in Tanzania and other institutions elsewhere with a similar research environment.…”
Section: Researchers' Self-efficacy Fears and Misconceptionssupporting
confidence: 90%
“…The other reasons that were highly ranked included: the likelihood that open access publications would be misused or plagiarised (51%); the general perception that open access publications were of low quality compared to traditional publications (55,2%); and researchers' worry about the long-term availability of open access publications (35,4%). These findings corroborate previous studies that found that uncertainties over later publishing of open access articles elsewhere, violation of publishers' copyrights, and plagiarism of open access papers are among the cited respondents' deterrents for their contribution to institutional repositories (Fang and Zhu 2006;Foster and Gibbons 2005;Hirwade and Rajyalakshmi 2005;Kim 2006;Pickton 2005;Ware 2004;Xu 2005). It is necessary to address these challenges to foster the adoption of open access in Tanzania and other institutions elsewhere with a similar research environment.…”
Section: Researchers' Self-efficacy Fears and Misconceptionssupporting
confidence: 90%
“…However, there are two categories of platforms which, when appropriately combined and customized, may result in the desired system: repository systems and spatial data infrastructure frameworks. The first category, web-based repository systems (Roy, 2015;Simons & Richardson, 2013;Ware, 2004), are able to store any kind of digital item, to keep metadata in accordance with recognized standards, to offer strong searching and browsing utilities, and to support the whole content depositing process.…”
Section: System Requirements and Designmentioning
confidence: 99%
“…It is an institutionally defined collection of scholarly research outputs that provide open or free access to all users within and outside the institution and complies with global standards for interoperability [1]. Institutional repositories have increasingly been recognized as important tools for scholarly communication and are a key source of institutional visibility and a workable tool for knowledge management within an institution.…”
Section: Introductionmentioning
confidence: 99%